2020
DOI: 10.1515/ijfe-2018-0351
|View full text |Cite
|
Sign up to set email alerts
|

Rheological properties of soy protein isolate – carboxymethyl flaxseed gum mixed dispersions under large amplitude oscillatory shear

Abstract: Carboxymethyl flaxseed gum (CMFG) is developed in our laboratory by modifying flaxseed gun through carboxymethylation. The aim of this study is to reveal the rheological properties of soy protein isolate – carboxymethyl flaxseed gum (SPI-CMFG) mixed dispersion in realistic processing conditions by conducting large amplitude oscillatory shear (LAOS) test, with consideration of concentration and degree of substitution (DS) of CMFG. Results showed that increasing CMFG concentration significantly increased storage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…rheology of soy protein isolate-carboxymethyl flaxseed gum (SPI-CMFG) mixtures (Ma, Niu, et al, 2020). The authors reported that the storage modulus, loss modulus, and apparent shear viscosity of the SPI-CMFG mixtures increased with increasing CMFG concentration.…”
Section: Large Deformation Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…rheology of soy protein isolate-carboxymethyl flaxseed gum (SPI-CMFG) mixtures (Ma, Niu, et al, 2020). The authors reported that the storage modulus, loss modulus, and apparent shear viscosity of the SPI-CMFG mixtures increased with increasing CMFG concentration.…”
Section: Large Deformation Experimentsmentioning
confidence: 99%
“…The LAOS method has been used to test several model plant‐based foods. For instance, it was used to quantify the impact of gum concentration on the rheology of soy protein isolate—carboxymethyl flaxseed gum (SPI‐CMFG) mixtures (Ma, Niu, et al, 2020). The authors reported that the storage modulus, loss modulus, and apparent shear viscosity of the SPI‐CMFG mixtures increased with increasing CMFG concentration.…”
Section: Modeling Of Rheological Properties Of Solid‐like Plant‐based...mentioning
confidence: 99%
“…The LAOS method has been used to test several model plant-based foods. For instance, it was used to quantify the impact of gum concentration on the rheology of soy protein isolatecarboxymethyl flaxseed gum (SPI-CMFG) mixtures 90 . The authors reported that the storage modulus, loss modulus, and apparent shear viscosity of the SPI-CMFG mixtures increased with increasing CMFG concentration.…”
Section: Large Deformation Experimentsmentioning
confidence: 99%